Pengaruh Digital Marketing dan Influencer Terhadap Keputusan Pembelian Produk UMKM Kuliner Di Kota Tanggerang Di Masa COVID-19 - Eneng Wiliana; Nining Purwaningsih (MAMEN: Jurnal Manajemen, 2022)
The Covid-19 pandemic has a direct impact on various aspects of the community's economy, especially Micro, Small and Medium Enterprises (UMKM). Many UMKM have decreased turnover, however, including UMKM in the culinary sector. The pandemic condition has changed MSMEs to switch to digital technology and the use of the internet in their business. This study aims to determine the Effect of Digital Marketing and Influencers on Purchase Decisions for UMKM Culinary Products in Tangerang City during the Covid-19 Period. This research method uses quantitative research, data collection techniques using questionnaires related to digital marketing, influencers and purchasing decisions, where the sample in this study were the perpetrators of Culinary UMKM in Tangerang City with a total sample of 63. The technical analysis used was regression analysis. The results of the analysis show both partially and simultaneously that the digital marketing variable, influencer has a positive and significant effect on purchasing decisions.